Significance of apoptotic markers Bcl-2, CD4+ T cells, hepatocyte growth factor and metalloproteinase -9 in infected patients with HCV - Eman R.Youness, M .El Nemr, Hoda M.El Azizy and Hanan F. Aly (Journal of Applied Pharmaceutical Science, 2013)
To examine the possible involvement of human B-cll leukemia /lymphoma 2(Bcl2) , CD 4+ cells , hepatocyte growth factor (HGF) and metalloproteinase -9 ( MMP-9), in the development of liver diseases caused by HCV infection, serum activities of these biomarkers were demonstrated by quantitave detemination of Enzyme Linked Immunosorbant Assay(ELISA) . Two groups of subjects (60 for each) were examined in this study: healthy control and patients with chronic hepatitis C(HCV) The results showed significant decrease in Bcl-2 (P≤ 0.0001) , and CD 4+ (P≤0.001) , while significant increase in HGF and MMP-9(P≤0.05). These findings imply an influence of these biomarkers by the existence of virus that might influence the following progression of liver disease, and a distinction between the pathological mechanisms of HCV. Since the serum MMP-9 activity were significantly varied between each stage of liver disease, an individual profile of these parameters might serve as an easy accessing serum marker to monitor the progression of liver disease.
Keywords: HCV, MMP-9, Bcl-2, CD 4+ and HGF.